Predictivity of bioimpedance phase angle for incident disability in older adults. Issue 1 (22nd August 2019) - Uemura, Kazuki; Doi, Takehiko; Tsutsumimoto, Kota; Nakakubo, Sho; Kim, Min‐Ji; Kurita, Satoshi; Ishii, Hideaki; Shimada, Hiroyuki
Abstract: Background: Bioelectrical impedance analysis (BIA)‐derived phase angle is expected to be an efficient prognostic marker of health adverse events with aging as an alternative of muscle mass. We aimed to examine the predictive ability of phase angle for incident disability in community‐dwelling elderly and determine the optimal cut‐off values. Methods: Community‐dwelling elderly aged ≥65 years ( n = 4452; mean age = 71.8 ± 5.3 years, 48.3% women) without disability at baseline participated in this prospective cohort study. Phase angle and appendicular skeletal muscle mass (ASM) were examined using a multi‐frequency BIA at baseline. Other potential confounding factors (demographics, cognitive function, depressive symptoms, medications, and physical performance) were also assessed. Incident disability was monitored on the basis of long‐term care insurance certification. Results: Over a follow‐up of 24 months, 4.0% ( n = 174) experienced disability, with an overall incidence rate of 20.6 per 1000 person‐years. The Cox hazard regression analysis showed that phase angle, as a continuous variable, was independently associated with incident disability after adjusting the covariates [male: hazard ratios (HRs) = 0.61, 95% confidence interval (CI) = 0.37–0.98; female: HR = 0.58, 95% CI = 0.37–0.90], although body mass index adjusted ASM was not. Receiver operating characteristic analysis indicated moderate predictive abilities of phase angle for incident disability [male: area under the receiver operating characteristic curve (AUC) = 0.76, 95% CI = 0.70–0.83; female: AUC = 0.71, 95% CI = 0.65–0.76], while those of body mass index adjusted ASM were low (male: AUC = 0.59, 95% CI = 0.521–0.66; female: AUC = 0.58, 95% CI = 0.52–0.63). Multivariate Cox regression analysis showed that low phase angle categorized by cut‐off value (male, ≤4.95°; female, ≤4.35°) was independently related to increased risk of incident disability (HR = 1.95, 95% CI = 1.37–2.78). Conclusions: Lower phase angle independently predicts the incident disability separately from known risk factors. BIA‐derived phase angle can be used as a valuable and simple prognostic tool to identify the elderly at risk of disability as targets of preventive treatment.